Some solvable non-linear equations related to aerodynamic instability phenomena - Bich, Nguyen Dang; Thong, Nguyen Vo (Vietnam Journal of Mechanics, 1994)
This article proposes some forms of aerodynamic forces, looks for accurate solutions of core - pendent non-linear differential equations and analyses the characteristics of aerodynamic forces and of equation’s solution. Found solutions proves that aerodynamic forces are formed from two elements: element of non-linear and dispersion, that single solutions are usually found and aerodynamic instability easy occurs.